Embracing Technology and the Challenges of Complexity - Alice Robbin (tripleC: Communication, Capitalism & Critique)
Advances in new digital platforms, innovative applications, and the convergence of computer, information, and communication technologies are transforming our everyday lives. ICTs have consequences for governance, community, work, information, knowledge, human communication, and well being, to name only a few. We live in a world where change is a constant, where interdependencies are multiple, heterogeneous, and increasingly fragile, and where uncertainty, ambiguity, incomplete information, and unanticipated consequences are the norm. The outcomes of our engagement with technology are complex and unpredictable. They defy simple conclusions because they are historical, temporal, situational, and embedded. Moreover, they are problematic and surprising: inconsistent, paradoxical, disorderly, contradictory, and contingent. In this talk I want to examine some of the empirical evidence about the complexity of our technological landscape and suggest ways to make sense of what is happening through theoretical frameworks drawn from different disciplinary traditions. Following Nobel Laureate in Economics Elinor Ostrom, our aim should be to “dissect and harness complexity rather than eliminate it” so that we can create responsive and resilient systems.